A virtual reality design for learning the basic concepts of synchrotron light source. (22nd August 2011) - Tarng, Wernhuar; Lin, Chih Ming; Liu, Yen Tzu; Tong, Yu Neng; Pan, Kuan Yeu
This study investigated the virtual reality technology to develop a virtual synchrotron light source model and its learning contents for applications in the curriculum of science and life technology in elementary and junior high schools. The objective is to increase the interest and effectiveness of young students in learning this advanced technology and its applications. The factors of student age, gender and correlation with the performance in previous science courses were also investigated to see if they would affect the learning effectiveness. A teaching experiment was conducted and the results showed that the model was effective in helping students understand the basic concepts of synchrotron light source and its applications. Student's age and gender had no obvious influence on the learning achievement, but a significant positive correlation was found between students' performance in their previous science courses and the learning achievement. Also, the questionnaire results revealed that most students were very interested in using the virtual light source model and its learning contents.